Extramedullary haematopoiesis in patients with thalassemia: a cross-sectional description of its prevalence, clinical features and survival - Eduardo Cerello Chapchap; Murilo Marques Almeida Silva; Ronaldo Hueb Baroni; Aderson da Silva Araujo; Reijane Alves de Assis; Sandra Regina Loggetto; Antonio Fabron Junior; Monica Pinheiro de Almeida Verissimo; Giorgio Roberto Baldanzi; Kleber Yotsumoto Fertrin; Fernando Tricta; Antonio Giulio Piga; et al. (Hematology, Transfusion and Cell Therapy)
Introduction: Despite knowledge advances on extramedullary haematopoiesis (EMH) in thalassemic patients, the real picture remains an open issue. Objectives: To assess EMH prevalence in patients with thalassemia major (TM) and intermedia (TI), to describe magnetic resonance imaging (MRI) findings and to explore clinical risk factors. Methods: In this cross-sectional study, images and clinical records of 184 consecutive patients with thalassemia who underwent T2* MRI between 2004 and 2011 were reviewed. Association of EMH with survival was investigated for patients with available follow-up charts. Results: EMH was detected in 16/168 (9.5%) patients with TM (aged 19-49 years) and in 3/16 (18.8%) with TI (aged 36-41 years). Most (88%) had paravertebral thoracic and/or abdominal masses. Age was significantly associated with EMH risk (hazard ratio, [HR] 1.10/year; confidence interval [CI]: 1.03-1.18; p-value < 0.001), while lower pancreatic iron content by T2*MRI (HR: 0.94/ms; CI: 0.89-0.99; p-value = 0.049) was a protective factor. Estimated survival rate was superior for EMH-positive (n = 19) when compared to EMH-negative patients (n = 75) (p-value = 0.013). Conclusions: The prevalence of EMH was 10.3% (19/184), presented mainly as tumoral masses of 3 to 10 cm. Age was a risk factor for EMH development, while lower pancreatic iron might be a protective factor in this cohort.